NLRP6 deficiency expands a novel CD103+ B cell population that confers immune tolerance in NOD mice - Pearson, James A.; Peng, Jian; Huang, Juan; Yu, Xiaoqing; Tai, Ningwen; Hu, Youjia; Sha, Sha; Flavell, Richard A.; Zhao, Hongyu; Wong, F. Susan; Wen, Li (Frontiers in Immunology, 2023)
Gut microbiota have been linked to modulating susceptibility to Type 1 diabetes; however, there are many ways in which the microbiota interact with host cells, including through microbial ligand binding to intracellular inflammasomes (large multi-subunit proteins) to initiate immune responses. NLRP6, a microbe-recognizing inflammasome protein, is highly expressed by intestinal epithelial cells and can alter susceptibility to cancer, obesity and Crohn’s disease; however, the role of NLRP6 in modulating susceptibility to autoimmune diabetes, were previously unknown. Therefore, we generated NLRP6-deficient Non-obese diabetic (NOD) mice to study the effect of NLRP6-deficiency on the immune cells and susceptibility to Type 1 diabetes development. NLRP6-deficient mice exhibited an expansion of CD103+ B cells and protection from type 1 diabetes. Moreover, NLRP6-deficient CD103+ B cells express regulatory markers, secreted higher concentrations of IL-10 and TGF1 cytokines and suppressed diabetogenic T cell proliferation, compared to NLRP6-sufficient CD103+ B cells. Microarray analysis of NLRP6-sufficient and -deficient CD103+ B cells identified 79 significantly different genes including genes regulated by lipopolysaccharide (LPS), tretinoin, IL-10 and TGF, which was confirmed in vitro following LPS stimulation. Furthermore, microbiota from NLRP6-deficient mice induced CD103+ B cells in colonized NLRP6-sufficient germ-free mice; however, the long-term maintenance of the CD103+ B cells required the absence of NLRP6, or continued exposure to NLRP6-deficient microbiota. Together, our data indicate that NLRP6 deficiency promotes expansion and maintenance of a novel TGFβ1-dependent CD103+ Breg population. Thus, targeting NLRP6 therapeutically may prove clinically useful.